If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 72 + -3x = 24x + 24 Reorder the terms: 72 + -3x = 24 + 24x Solving 72 + -3x = 24 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. 72 + -3x + -24x = 24 + 24x + -24x Combine like terms: -3x + -24x = -27x 72 + -27x = 24 + 24x + -24x Combine like terms: 24x + -24x = 0 72 + -27x = 24 + 0 72 + -27x = 24 Add '-72' to each side of the equation. 72 + -72 + -27x = 24 + -72 Combine like terms: 72 + -72 = 0 0 + -27x = 24 + -72 -27x = 24 + -72 Combine like terms: 24 + -72 = -48 -27x = -48 Divide each side by '-27'. x = 1.777777778 Simplifying x = 1.777777778
| 5y+3y=8 | | 17-6.10*2+12= | | 9x-7=29 | | 112=4x | | 0.4x+3=0.8x+1 | | x^2+14x=72 | | 4(x-2)+8x=-44 | | 3/10(x-2)=3 | | 8x+45=17x-1 | | -18=5c | | 21-x/2=x/4 | | 17-6.10+2+12= | | x+.50x=10 | | 15-3f=2g | | m-n=3 | | 60=10-10x | | 6x+16=16-64 | | 4h-12=12-4n | | n^2-3n-14=0 | | m+n=3 | | 5-9x=41-37x | | -19n+6=-17n-6 | | x-5/9=x+5/5 | | 5y-1=3y+1 | | (x-3)(x-5)-8=0 | | -2+10=16x-3-15x | | 3e=9/4 | | 4x-29=2x+3 | | 0=-20+b | | x-15=-135 | | 13-10x=36-17x | | 5y-17y=-64-80 |